Citrus Nutrition Management Practices - Jamie D. Burrow; Tripti Vashisth; Mongi Zekri; Stephen H. Futch; Arnold Schumann (EDIS)
This document is a quick guide to citrus nutrient deficiencies and the importance of a balanced nutriton program.